When prices hardly matter: Incomplete insurance contracts and markets for repair goods - Martin Nell; Andreas Richter; Jörg Schiller (Hamburg University, Institute for Risk and Insurance, 2005)
This paper locks at markets charaterized by the fact that the demand side is insured. In these markets a consumer purchases a good to compensate consequences of unfavorable events, such as an accident or an illness. Insurance policies in most lines of insurance base indemnity on the insured's actual expenses, i. e., the insured would be partially or completely reimbursed when purchased certain goods. In this setting we discuss the interaction between insurance and repair markets by focusing, on the one hand, upon on development of prices and the market structure in markets with insured customers, and, on the other hand, the resulting backlash on optimal insurance contracting.
Keywords: C72; D43; G22; 330; insurance; incomplete contracts; repair markets